2008
DOI: 10.1002/ijc.23591
|View full text |Cite
|
Sign up to set email alerts
|

Family history of prostate cancer and prostate cancer risk in the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention (ATBC) Study

Abstract: Prostate cancer family history has been associated with increased risk of the malignancy. Most prior studies have been retrospective and subject to recall bias, however, and data evaluating interactions with other important risk factors are limited. We examined the relationship between a family history of prostate cancer and prostate cancer risk in relation to body size, micronutrients and other exposures in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Study cohort of Finnish male smokers. Fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
1
27
1
1
Order By: Relevance
“…No other study has reported on the height -prostate cancer relationship according to age. Two studies reported somewhat stronger associations with advanced/aggressive disease in men with a positive family history of prostate cancer (Norrish et al, 2000;Ahn et al, 2008). The limited numbers of aggressive cases with a first-degree family history (n ¼ 109), prevented our examining potential interaction with family history.…”
Section: Discussionmentioning
confidence: 98%
“…No other study has reported on the height -prostate cancer relationship according to age. Two studies reported somewhat stronger associations with advanced/aggressive disease in men with a positive family history of prostate cancer (Norrish et al, 2000;Ahn et al, 2008). The limited numbers of aggressive cases with a first-degree family history (n ¼ 109), prevented our examining potential interaction with family history.…”
Section: Discussionmentioning
confidence: 98%
“…Fifteen prospective cohorts (922) (Table 1) within this international consortium met the predefined criteria for inclusion: baseline assessment of usual diet, validation of the dietary assessment method used or a closely related instrument, at least one publication on an association between diet and cancer, and identification of at least 50 incident CaP cases during follow-up. Each study received approval from the institutional review board of their institution.…”
Section: Methodsmentioning
confidence: 99%
“…Incident CaP cases were identified in each study by follow-up questionnaires with subsequent review of medical records (20,21), linkage to cancer registries (1218,23), or both (911,22), with the exception of the Prostate Cancer Prevention Trial (PCPT), for which cases were limited to those diagnosed through biopsy performed because of an elevated PSA or suspicious digital rectal exam (“for cause”) per trial protocol (19). Some studies also used mortality registries to identify CaP deaths (10,12,14,15,17,20,22,23).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a large nested case-control study (included in the ATBC Cancer Prevention Study cohort) a statistically significant inverse dose-response relationship was found between plasma PLP levels and pancreatic cancer risk: the risk of subjects in the highest PLP tertile was half the risk of the subjects in the lowest tertile (OR = 0.48). Several case-control studies have found that high vitamin B6 intake was associated with a decreased risk of gastric adenocarcinomas (Michaud et al, 2002;Ahn et al, 2008;Similä et al, 2009) and oral or pharyngeal cancer (Negri et al, 2000).…”
Section: Vitamin B6 Deficiency Genome Instability and Cancermentioning
confidence: 99%